Vegetation Spatial Distribution on Taean Duung Wetland Protect Area - Haeseon Shin; Sanghun Lee; Sangwook Han (Geo Data, 2024)
In this study, we conduct for providing information on the status of vegetation space distribution in the Duung wetland protected area and to help manage the wetland protected area. To understand the spatial distribution of vegetation in Duung Wetland, used the results of surveys in 2019 and 2023. As a result of the study, the number of vegetation types increased by 4 from 20 to 24. Four communities were newly investigated, including the Utricularia tenuicaulis community, Pueraria montana var. lobata-Elymus tsukushiensis community, Spiraea prunifolia for. simpliciflora community, and Miscanthus sinensis var. purpurascens community. In accordance with the environment, the range of aquatic plant communities such as Trapa japonica community and Nymphaea tetragona var. angusta community increased, and the succession zone of cultivated land expanded dry grassland. The survey results can be used as basic data for systematic management of the Duung wetland protected area.